STRUCTURAL ELUCIDATION OF BIOACTIVE SECONDARY METABOLITES FROM ENDOPHYTIC FUNGUS - Verma, Shiv Kr; Lal, Moti; Das, Mira Debnath (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: In this research for bioactive secondary metabolites from endophytic fungal isolate CPR5, which was later identified and characterized as Aspergillus niger sp. Methods: Eight bioactive compounds (1-8) were isolated and purified using a series of chromatographic techniques and identified by applying 13C and 1H nuclear magnetic resonance and mass (ESI-MS spectrometry). Results: All the compounds were tested for antimicrobial activity against a wide range of human and plant pathogenic bacteria as well as fungi. These microorganisms were, Xanthomonas oryzae, Escherichia coli, Streptococcus pneumonia, Bacillus subtilis, Staphylococcus hyicus, Bacillus sphaericus, Staphylococcus aureus, and Pseudomonas aeruginosa, Candida albicans, Sclerotium rolfsii, Sclerotinia, scleratiourum, and Phoma exigua minimum inhibitory concentration value have also been determine for these microorganism. Conclusion: In this study, a total 10 endophytic fungi were isolated from the Calotropis procera, show a great antibacterial activity against 24 human pathogenic bacteria.